A laser rangefinder for robot control and inspection - Parthasarathy, Sarangarajan; Birk, J.; Dessimoz, J. (Proc. of Photo-Optical Instrumentation Engineers, Robot VIsion, 1982)
Three-dimensional surface point data is often useful for r0b0t control and inspection casks. The design of sensors for collecting this data involves many choices, with selections made on the basis of data rate, accuracy, field of view, safety, size, object properties, and the need for registered range and brightness data. A sensor has been designed with data rates of 30 kHz for brightness, 2 kHz for range in the scanning mode, and 250 Hz for range in the random access mode. Range data accuracy is about .1A of the field of view. The main components of the sensor are a low power laser (1 mW), a 1024 element COD linear array camera, a galvanometer scanner, and a special interface to a minicomputer. Alternative designs include stereo without using projected energy, white light projection, ultrasound, time-of-flight measurements, multiple detectors, projecting planes versus beams, two-dimensional array cameras and "position" sensors, and a variety of scanning mechanisms.